(untitled) ("Journal "U". Economy. Management. Finance.", 2024)
This article examines the concept of a program-project approach, identifies its specific features and advantages, examines the pyramid of organizational changes when introducing a program-project approach into the system of state and municipal governance, and studies the effectiveness of its application using national projects as an example.